ANALISIS PENGARUH KEMAMPUAN KARYAWAN, PEMBAGIAN TUGAS, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. PELABUHAN INDONESIA II (PERSERO) CABANG PALEMBANG - SEVVY YOSSA; ZUNAIDAH . (Program Studi Magister Manajemen FE Unsri, 2013)
This study aimed to determine the effect of the employee abilities, job description, motivation together as well as partial to determine the dominant influence on the performance ofÂ PT. Pelabuhan Indonesia II (Persero) Palembang Branch. The research was conducted in PT. Pelabuhan Indonesia II (Persero) Palembang Branch as many as 102 respondents. The sampling technique in the study conducted by using census sampling methods, data analysis techniques used are statistical analysis, including multiple linear regression analysis, analysis simultaneously (F test), the partial analysis (t test) and analysis coefficient of determination. The test results show that employee abilities, job description, and motivation together affect the performance of PT. Pelabuhan Indonesia II (Persero) Palembang Branch.Â Job description is partially significantly and dominat influence the performance of PT. Pelabuhan Indonesia II (Persero) Palembang Branch. In this research, job description is a significant factor on the performance of employees, therefore the company should pay attention to the empty vacancy Â in some parts and filled with individuals who are competent in their field to avoid overlapping authority and accumulation of workload in each respective division.